MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBANTUAN MEDIA ANIMASI TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS III SD - Ni Komang Delia July Anggraeni; Gusti Ayu Putu Sukma Trisna; Ketut Herya Darma Utami (STKIP Subang, 2026)
The reading comprehension ability of third-grade elementary school students is still low despite the implementation of various conventional teaching strategies. This gap hinders the achievement of the Pancasila Student Profile in the Merdeka Curriculum. This study analyzes the effect of the Cooperative Script learning model assisted by Canva animation media on the reading comprehension ability of lower-grade elementary school students. A quasi-experimental study with a Non-Equivalent Post-Test Only Control Group Design was used in this study. The research subjects consisted of 47 third-grade elementary school students, with 29 students in the experimental group and 18 students in the control group. Data were collected through a 20-item multiple-choice test measuring Bloom's taxonomy levels C1-C6 in narrative texts, validated for content by two experts, and tested for reliability using KR-20. Data analysis included descriptive statistics, Shapiro-Wilk normality test, Levene's homogeneity test, and independent t-test with pooled variance. The research results analyzed a significant increase in reading comprehension skills in the experimental group that received the Cooperative Script model assisted by Canva animation compared to the control group. The visual collaborative model proved to optimize comprehension from literal to critical levels through alternating oral summaries and dynamic text visualizations. This study concludes that integrating the Cooperative Script with digital animation media is effective in closing the elementary literacy gap, supporting essential learning in the Independent Curriculum. Its implications include producing ready-to-use teaching modules for Indonesian language teachers and recommendations for digital literacy policies in elementary school clusters.